Regulation and Investment Incentives in Electricity Distribution - Astrid Cullmann; Maria Nieswand (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper we analyze the investment behavior of electricity distribution companies. First, we test the hypothesis if the implementation of an incentive-based regulatory scheme with revenue caps impacts the firms' investment decisions in general. Second, we test if the specific regulatory design to determine the revenue caps impacts the firms' investment behavior. The analysis is based on a unique and detailed firm level data for German electricity distribution companies over the 2006-2012 period. Controlling for a large amount of firm specific heterogeneity and ownership, we show that the investment rate is higher after the implementation of incentive regulation in 2009. Furthermore, we find that the design with its specific institutional constraints for determining the revenue-caps, influence the investment decisions of the firms. Especially in the base year, when the rate base is determined for the following regulatory period, investments increase. The analysis demonstrates that the whole design of incentive regulation must be taken into account for a sound assessment of investment behavior in electricity distribution.
Keywords: L94; L51; D22; 330